Perancangan Analisa Risiko Berbasis ISO 9001:2015 dan FSSC 22000 di PT Hapete Surabaya - Descelly Cristiani; Jani Rahardjo (Jurnal Titra, 2018)
PT Hapete is a manufacture company which specializes in production yarn for industrial manufacture who apply ISO 9001 and FSSC 2200 to maintain the safety and quality of their product. The purpose of this reasearch is to design the risk assesment to complete the requirement of ISO 9001:2015 and FSSC 22000. Risk analysis designing uses Failure Mode and Effect Analysis (FMEA) method, for ISO 9001:2015 will be implemented in all departements, and for FSSC 22000 will be implemented in departements who producing food grade product. Risk analysis was conducted in 20 departements, and found 1054 possible risk. Three of the 1054 risk found were classified into high risk categories. The three risk that are high risk is dirty yarn on the winding division, the number of customer payments that do not match the amount of billing, and mistakes in making delivery order. The overall suggested mitigation plan is to communicate with related parties to get decision together, so the problem can be solved. PT.Hapete needs to focus on the risk in the departement which is directly related to product, cash flow, dan customers sastifaction. For food grade products supervision needs to be done on the delivery process.